2001
DOI: 10.1093/emboj/20.6.1259
|View full text |Cite
|
Sign up to set email alerts
|

The role of Plo1 kinase in mitotic commitment and septation in Schizosaccharomyces pombe

Abstract: Plo1-associated casein kinase activity peaked during mitosis before septation. Phosphatase treatment abolished this activity. Mitotic Plo1 activation had a requirement for prior activation of M-phase promoting factor (MPF), suggesting that Plo1 does not act as a mitotic trigger kinase to initiate MPF activation during mitotic commitment. A link between Plo1 and the septum initiating network (SIN) has been suggested by the inability of plo1D cells to septate and the proli®c septation following plo1 + overexpres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
140
0
4

Year Published

2001
2001
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 138 publications
(154 citation statements)
references
References 58 publications
(98 reference statements)
10
140
0
4
Order By: Relevance
“…However, Plo1 localizes to the SPB after mitotic entry and delocalizes from it following APC activation (Mulvihill et al, 1999). Close examination of Plo1 activities with synchronous cultures revealed that Plo1 activation occurs in a biphasic manner; the first phase of Plo1 activity coincides with actin ring formation in prophase, whereas the second peak precedes septum formation late in mitosis (Tanaka et al, 2001). These data suggest that timely activation and dynamic subcellular localization of Plo1 are critical for regulating Plo1 function.…”
Section: Regulation Of Protein Synthesis and Degradationmentioning
confidence: 90%
“…However, Plo1 localizes to the SPB after mitotic entry and delocalizes from it following APC activation (Mulvihill et al, 1999). Close examination of Plo1 activities with synchronous cultures revealed that Plo1 activation occurs in a biphasic manner; the first phase of Plo1 activity coincides with actin ring formation in prophase, whereas the second peak precedes septum formation late in mitosis (Tanaka et al, 2001). These data suggest that timely activation and dynamic subcellular localization of Plo1 are critical for regulating Plo1 function.…”
Section: Regulation Of Protein Synthesis and Degradationmentioning
confidence: 90%
“…These include 1) mitotic abnormalities caused by the formation of a monopolar mitotic spindle; 2) misplaced actomyosin rings; and 3) cytokinesis defects associated with the formation of multinucleate cells with back-to-back nuclei, similar to that observed in SIN mutants (Ohkura et al, 1995;Bähler et al, 1998;Tanaka et al, 2001). The plo1 ts mutants used in this study display all the abovementioned phenotypes at the restrictive temperature of 36°C but rarely do so at the permissive temperature of 24°C.…”
Section: Interaction Of Pdk1 With Fission Yeast Polo-kinase Plo1mentioning
confidence: 67%
“…The architecture of the filamentous actin ring that implements cytokinesis was defective in both the plo1.ts4 and plo1.ts18 mutant strains (Figure 3; Tanaka et al, 2001). At 25 • C both strains had an actin ring that correctly bisected the cell perpendicular to the long axis of the cell (Marks and Hyams, 1985).…”
Section: Phenotypic Analysis Of Plo1ts4 and Plo1ts18mentioning
confidence: 99%
“…pombe 593 in plo1.ts18 mutant cells was much larger than normal and appeared to randomly bisect the cell in a manner that was highly reminiscent of the plo1.1, plo1.24C and plo1.25 mutations reported by Bähler et al (1998a; Figure 3B). The ability of plo1.ts4 to use the F-actin ring to deposit septal material was severely compromised when the strain was grown in minimal medium (Tanaka et al, 2001); 4 h after the temperature was changed from 25 • C to 36 • C, 49% of cells contained multiple nuclei but had no septa (Tanaka et al, 2001). The few septa that did form in plo1.ts4 cells were misshapen and asymmetric (Tanaka et al, 2001).…”
Section: Phenotypic Analysis Of Plo1ts4 and Plo1ts18mentioning
confidence: 99%
See 1 more Smart Citation